THE INFLUENCE OF COMPETENCY DEVELOPMENT ON THE COMPETITIVE ADVANTAGE OF SALT FARMERS IN GALIS DISTRICT, PAMEKASAN REGENCY - Sukron Ma’mun; Abdurahman Abdurahman; Erina Saputri; Mohammad Bustanol Husein (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research is motivated by the problem of many salt farmers in the Galis District who do not understand the importance of developing competence and competitive advantage for the sustainability of the salt business. This research aims to determine and analyze the influence of competency development on the competitive advantage of salt farmers in Galis District, Pamekasan Regency. The research method used is a quantitative method so the data displayed is data from questionnaire results which are processed using SPSS 26 statistics. The type of research used in this research is survey research, data collected through questionnaire results on the research instrument used. The data analysis technique used is the inferential statistical analysis technique. The results of this research can conclude that competency development has a significant effect on the competitive advantage of salt farmers in Galis District, Pamekasan Regency. This research is expected to contribute to competency development efforts to increase the competitive advantage of salt farmers in Galis District, Pamekasan Regency.